Cross-linguistic and cross-disciplinary studies of academic discourse: Challenges for the researchers - Šinkūnienė, Jolanta (Kalbotyra, 2015)
Recent trends in academic discourse analysis reveal a keen scholarly interest in cross-disciplinary and cross-linguistic variation in academic texts. While most of the research is still on the English language, the last few decades have seen an upsurge of interest in academic discourse produced in other languages, frequently comparing it to patterns of writing and argumentation in Anglo-American scientific texts. Numerous studies attempt to outline the universal features of academic discourse as well as to highlight the specific ones, typical only of some of the disciplines or cultural communities. Thus, features of academic discourse are often interpreted within the “big” (i. e. national) and “small” (i. e. disciplinary) culture context (cf. Atkinson 2004). The paper briefly reviews trends in current academic discourse research, mainly in the genre of the research article. The purpose of the paper is to discuss the challenges that researchers of academic discourse face while compiling specialized comparable corpora for their cross-disciplinary and cross-linguistic analyses and to highlight certain methodological issues which are important in this type of analyses. As noted by many researchers in the field, the reliability of the results and a better empirical grounding primarily depend on the appropriately selected common ground of comparison. An overview of recently published research on cross-linguistic and cross-disciplinary aspects of academic discourse reveals various methodological solutions to corpus design and data analysis.